The mystery of Edwin Drood - Dickens, Charles, 1812-1870.; Garfield, Leon. (1980)
Introduces an array of characters, from the sinister to the comic, and moves to a haunting climax in an atmospheric murder mystery that features the seemingly benevolent John Jasper, a secret opium addict, and his relationship with his newly engaged nephew, Edwin Drood.
A Chronology of Charles Dickens -- The Mystery of Edwin Drood -- Manuscript List of Projected Names and Titles -- The Number Plans -- The Sapsea Fragment.
Also issued online.
Keywords: Choral conductors -- Fiction; Missing persons -- Fiction; Cathedrals -- Fiction; Fiction; England -- Fiction; Psychological fiction